Hippocampal Abnormalities after Prolonged Febrile Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Hippocampal volume and T2 relaxation times were determined in an MRI study of 14 children with prolonged febrile convulsions (PFC) who were investigated, 1) within 5 days of a PFC, and 2) at follow-up 4-8 months after the acute study, at the Institute of Child Health, University College, and Great Ormond Street Hospital, London, UK.